Trends in Incidence, and Mortality of Acute Exacerbation of Chronic Obstructive Pulmonary Disease in the United States Emergency Department (2010–2018). (3rd September 2021) - Nguyen, Paul L.; Uddin, Mohammed M.; Mir, Tanveer; Khalil, Amir; Regmi, Neelambuj; Pervaiz, Amina; Hussain, Tanveer; Babu, Mohammed Amir; Ullah, Irfan; Patel, Pragnesh; Lohia, Prateek; Saydain, Ghulam; et al.
Abstract: Literature regarding trends of incidence, mortality, and complications of acute exacerbation of chronic obstructive pulmonary disease (COPD) in the emergency departments (ED) is limited. What are trends of COPD exacerbation in ED? Data were obtained from the Nationwide Emergency Department Sample (NEDS) that constitutes a 20% sample of hospital-owned EDs and inpatient sample in the US. All ED encounters were included in the analysis. Complications of AECOPD were obtained by using ICD codes. Out of 1.082 billion ED encounters, 5, 295, 408 (mean age 63.31 ± 12.63 years, females 55%) presented with COPD exacerbation. Among these patients, 353, 563(6.7%) had AECOPD-plus (features of pulmonary embolism, acute heart failure and/or pneumonia) while 4, 941, 845 (93.3%) had exacerbation without associated features or precipitating factors which we grouped as AECOPD. The AECOPD-plus group was associated with statistically significantly higher proportion of cardiovascular complications including AF (5.6% vs 3.5%; p < 0.001), VT/VF (0.14% vs 0.06%; p < 0.001), STEMI (0.22% vs 0.11%; p < 0.001) and NSTEMI (0.65% vs 0.2%; p < 0.001). The in-hospital mortality rates were greater in the AECOPD-plus population (0.7% vs 0.1%; p < 0.001). The incidence of both AECOPD and AECOPD-plus had worsened ( p -trend 0.004 and 0.0003) and the trend of mortality had improved ( p -trend 0.0055 and 0.003, respectively). The prevalence of smoking for among all COPD patients had increased ( p -value 0.004), however, the prevalence trend of smoking among AECOPD groups was static over the years 2010–2018. There was an increasing trend of COPD exacerbation in conjunction with smoking; however, mortality trends improved significantly. Moreover, the rising burden of AECOPD would suggest improvement in diagnostics and policy making regarding management.